Insights from stable isotopes of water and hydrochemistry to the evolutionary processes of groundwater in the Subei lake basin, Ordos energy base, Northwestern China. Issue 5 (3rd September 2019) - Liu, Fei; Song, Xianfang; Zhen, Pinna; Wang, Lishu; Wang, Shou
ABSTRACT: Changes in groundwater evolutionary processes due to aquifer overexploitation show a world-wide increase and have been of growing concern in recent years. The study aimed to improve the knowledge of groundwater evolutionary processes by means of stable water isotopes and hydrochemistry in a representative lake basin, Ordos energy base. Groundwater, precipitation, and lake water collected during four campaigns were analysed by stable isotopes and chemical compositions. Results showed that temperature effect predominated the isotope fractionation in precipitation, while evaporation and inadequate groundwater recharge were the key factors explaining high salinity and isotopic enrichment in lake water. Additionally, the Kuisheng Lake was a preferential area of groundwater recharge, while the Subei Lake received less sources from underlying aquifer due to the combined effects of low permeable zone and upstream groundwater captured by the production wells. The homogeneous isotope signatures of groundwater may be ascribed to the closely vertical hydraulic connectivity between the unconfined and the confined aquifers. Isotopically enriched groundwater pumping from well field probably promoted isotopic depletion in groundwater depression cone. These findings not only provide the conceptual framework for the inland basin, but also have important implications for sustainable groundwater management in other groundwater discharge basins with arid climate.